ENHANCING ASN PROFESSIONALISM: THE ROLE OF EDUCATION, TRAINING, AND MOTIVATION IN THE REGIONAL SECRETARIAT OF MALANG REGENCY - Yantri Pramodawardani; Setiyawan (CV. Radja Publika, 2025)
This study aims to analyze the effect of education and training on the professionalism index of State Civil Apparatus (ASN), with motivation as a moderating variable in the Regional Secretariat of Malang Regency. The data analysis method used is Structural Equation Modeling - Partial Least Squares (SEM-PLS), with a total sampling technique involving all 36 Sub-Division Heads as respondents. The results of the study indicate that education has a positive and significant effect on the ASN professionalism index, which means that the higher the level of ASN education, the better their professionalism. Likewise, training has a positive and significant effect on the ASN professionalism index, indicating that effective training can improve ASN professionalism. However, motivation as a moderating variable does not have a significant effect. Motivation only slightly increases the relationship between education and ASN professionalism, but the effect is not large enough to be considered significant. Meanwhile, motivation does not play a role in moderating the relationship between training and ASN professionalism. These findings indicate that improving ASN professionalism is more effective through direct education and training, without relying on motivational factors. Therefore, the policy to improve the quality of ASN should focus more on increasing access to relevant education and training.